2021
DOI: 10.1371/journal.pone.0250798
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between FDI, fiscal expenditure and green total-factor productivity in China: From the perspective of spatial spillover

Abstract: Deeply investigating the relationship between foreign direct investment (FDI), fiscal expenditure and green total-factor productivity (GTFP) is beneficial to formulating effective policies to promote the high-quality development in China. Based on theoretical mechanism analysis, with panel data of China’s mainland 30 provinces during 2003–2017, this paper utilizes spatial econometric model to empirically explore the effects of FDI, fiscal expenditure and their interaction item on the growth of GTFP in China. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 76 publications
1
12
0
Order By: Relevance
“…We draw on the methods of Wang et al [ 92 ], and divide the samples into high- and low-income countries according to per capita national income. Columns (5, 6) of Table 7 show the estimated results.…”
Section: Resultsmentioning
confidence: 99%
“…We draw on the methods of Wang et al [ 92 ], and divide the samples into high- and low-income countries according to per capita national income. Columns (5, 6) of Table 7 show the estimated results.…”
Section: Resultsmentioning
confidence: 99%
“…The institutional factor mostly means the government’s influence on the market economy. Wang et al suggested that it is necessary to give full attention to the synergy between FDI and fiscal expenditure and formulate regionally targeted policies to improve GTFP and promote high-quality development in China [ 27 ]. Song et al found that the expenditure decentralization and the fiscal expenditure competition among different areas are conducive to improving the local area’s GTFP [ 28 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A substantial body of existing research concerns the mechanisms of the fiscal decentralization affecting GTFP [ 48 , 49 ]. Song et al (2020) studied the effectiveness of decentralized fiscal authority on GTFP from a revenue perspective and an expenditure perspective, respectively [ 50 ].…”
Section: Literature Reviewmentioning
confidence: 99%